A New Species of the Scinax catharinae Group (Anura: Hylidae) From the Highlands of Santa Catarina, Brazil - Lourenco, Ana Carolina C. [UNESP]; Lingnau, Rodrigo; Haddad, Celio F. B. [UNESP]; Faivovich, Julian (Soc Brasileira Herpetologia, 2019)
We describe a new species of the Scinax catharinae group from the highlands of the State of Santa Catarina, southern Brazil. The new species is distinguished from the other species of the group for having a trapezoid interocular blotch, an externally distended vocal sac, hypertrophied forearms in males, and the extension of foot webbing on Toe V. This new species brings to 35 the number of species in the S. catharinae group, which stands as the most diversified endemic Jade of Atlantic forest frogs. The discovery of a new, distinctive species in the southern section of the Atlantic Forest, where so far only five species of this clade were known to occur, indicates that we are far from a good understanding of the taxonomic diversity of this species group.
Keywords: Morphology; Scinaxini; Taxonomy; Vocal sac